Coping Stres Istri Seorang TKI - Arifianda Lubis (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study examines the phenomenon of Indonesian labor migration abroad and its impact on the families left behind. The objective is to analyze the social and psychological aspects experienced by migrant workers’ spouses. The research employs a descriptive case study method with data source triangulation. The findings reveal that migrant couples often neglect social and psychological factors in their decision-making, affecting family relationships. Therefore, effective communication support and government policies are needed to enhance the well-being of migrant workers’ families.